2022
DOI: 10.1161/jaha.122.027103
|View full text |Cite
|
Sign up to set email alerts
|

Lipidome‐ and Genome‐Wide Study to Understand Sex Differences in Circulatory Lipids

Abstract: Background Despite well‐recognized differences in the atherosclerotic cardiovascular disease risk between men and women, sex differences in risk factors and sex‐specific mechanisms in the pathophysiology of atherosclerotic cardiovascular disease remain poorly understood. Lipid metabolism plays a central role in the development of atherosclerotic cardiovascular disease. Understanding sex differences in lipids and their genetic determinants could provide mechanistic insights into sex differences in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
21
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 55 publications
5
21
0
Order By: Relevance
“…In line with previous evidence for a sex difference in blood pressure 54 or lipid profile, 55,56 we found that sex significantly modulates the associations of 4 lipids, including CE(16:1), PC(32:1), PC(34:1), and PE(36:4) B, with the prevalence of hypertension in American Indians. The associations of longitudinal changes in 3 lipids, including FA(14:1), FA(16:1), and SM(d39:1) A, with change in SBP were also significantly different between men and women.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous evidence for a sex difference in blood pressure 54 or lipid profile, 55,56 we found that sex significantly modulates the associations of 4 lipids, including CE(16:1), PC(32:1), PC(34:1), and PE(36:4) B, with the prevalence of hypertension in American Indians. The associations of longitudinal changes in 3 lipids, including FA(14:1), FA(16:1), and SM(d39:1) A, with change in SBP were also significantly different between men and women.…”
Section: Discussionsupporting
confidence: 92%
“…With the exception of SM d42:6, many sphingolipids including SM d44:1 and SM d38:1 are more abundant in females compared to males. This is consistent with human data that shows a similar trend wheremost sphingomyelins are more abundant in females 33,34 . Notably, lipids with the greatest fold change contain polyunsaturated 22:6 fatty acyl, for example TG 22:6_22:6_22:6 (TG 66:18), TG 18:0_22:6_22:6 (TG 62:12) and PC 18:0_22:6 (PC 40:6).…”
Section: Unsupervised Clustering Revealed Better Association Of Metab...supporting
confidence: 93%
“…15). Higher male circulating TAG and APOB levels were also reported in humans 43,44 . These observations could be explained by a shift of TAGs to the liver in female mice, fitting with our model of higher hepatic VLDL uptake, possibly explaining why clearance of circulating VLDL-associated TAGs in humans is faster in women 16,45 .…”
Section: Resultsmentioning
confidence: 67%